Confinement of zinc oxide nanoparticles in ordered mesoporous silica MCM-41 - Lihitkar, P. B.; Violet, Samuel; Shirolkar, Mandar; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Materials Chemistry and Physics, 2012)
Mesoporous silica (MS) and zinc loaded MS composites have been synthesized and characterized using high resolution transmission electron microscopy, X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, N-2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Thermal treatment of the zinc loaded MS composite lead to the formation of ZnO-MS composite. The well ordered uniform pore structure of MS (pore size similar to 3.4 nm) is found to remain stable even after 30% Zn loading albeit decrease in the pore size 1.2 nm indicates the formation of ZnO inside the pores. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect; Energy spectroscopy for chemical analysis (ESCA); Mesoporous; Photoluminescence spectroscopy; Surface properties

Post-synthetically modified porous covalent framework (PCF) for high proton conduction - Samanta, Partha; Desai, Aamod; Anothumakkool, Bihag; Shirolkar, Mandar; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Porous Covalent Framework; Post-synthetic Modification; proton conduction